Economic feasibility of electrical power cogeneration from forestry biomass in an engineered wood panel industrial facility - Souza, André Gustavo Oliveira (Array, 2021)
The use of sugarcane bagasse, straw, and chaff for electrical power generation in sugar-ethanol mills has been established; more recently, the recovery of forest biomass has been increasing in an attempt to reduce the use of fossil fuels and to increase electrical power generation focused on self-consumption. The potential for power generation in this segment is considerable, but the use of biomass in cogeneration processes depends on an attractive return on investments. This study was designed to analyze the economic feasibility of investment in thermal and electrical power generation equipment that makes it possible to use forest and logging residues and wood chips to replace the current gas-fired power generation in an engineered wood panel industry facility (Scenario 1) or investment only in thermal generation equipment (Scenario 2). Results showed that the investment to replace natural gas with forest biomass is economically viable not only for the generation of both types of energy but also for the generation of thermal energy itself. High costs of energy inputs such as natural gas and electricity for the industry explain the results, despite the requirement for high investments in cogeneration systems.